Occurrence of gastrointestinal parasites in goats from the Western Santa Catarina, Brazil Ocorrência de parasitas gastrintestinais em caprinos na região oeste de Santa Catarina, Brasil - Radavelli W.M.* (2014)
This study aims to investigate the occurrence of gastrointestinal parasites in goats from the Western Santa Catarina, Brazil. Twenty four farms were analyzed in 17 different municipalities. Animals (n=217) from different production purposes (milk and meat) and age were randomly chosen. Fecal samples were collected from the rectum stored in plastic bottles and transported to the laboratory in portable coolers at 10 °C. The technique of centrifugal flotation with saturated sugar solution was carried out in order to investigate the presence of eggs, cysts, and oocysts of gastrointestinal parasites. In 88.9% of the investigated animals, it was observed that the presence of nematode eggs which belongs to the Strongylida order, after cultivation and larvae identification were identified as Haemonchus spp., Trichostrongylus spp., Teladorsagia spp., Cooperia spp., and Oesophagostomum spp. Eggs of Thysanosoma, Trichuris, Moniezia, and Neoascaris genus were also observed. Additionally, the presence of oocysts of Eimeria spp. and Cryptosporidium spp. as well as cysts of Giardia spp., and Entamoeba spp. were verified. In all the farms evaluated, the animals showed a single or mixed infection, with the highest occurrence of helminths belonging to the Haemonchus and Trichostrongylus genus, as well as the protozoan Eimeria.